Experimental investigation of flow boiling in rectangular mini/micro-channels of different aspect ratios without and with vapour venting membrane. (5th March 2020) - Mohiuddin, Ahmed; Loganathan, Raamkumar; Gedupudi, Sateesh
Highlights: Experimental studies on the influence of vapour venting membrane on flow boiling in micro-channels. Three different channel aspect ratios (0.31, 0.92 and 3.7) with a hydraulic diameter of 0.6 mm. Membrane (aspect ratio of 3.7) reduces the pressure drop by up to 60%. Membrane decreases or increases the heat transfer coefficient depending on the aspect ratio. Abstract: Two-phase microchannel heat sinks generate higher pressure drop along with higher heat transfer coefficient. Literature review indicates that the addition of a vapour venting membrane to a microchannel reduces the flow boiling pressure drop, but the literature does not report the effect of the channel aspect ratio with a vapour venting membrane. The present study experimentally investigates the influence of vapour venting on the flow boiling pressure drop and heat transfer of water in copper mini/micro-channels of three different aspect ratios – 0.31, 0.92 and 3.7, with a hydraulic diameter of 0.60 mm and a length of 40 mm. Experiments were conducted for two different cases – one with a Lexan cover on top and the other with a PTFE hydrophobic membrane on top of the channel. Two membranes of different pore sizes 0.22 μm and 0.45 μm were chosen. The mass fluxes maintained were 270, 450 and 650 kg/m 2 s and the channel heat flux varied from 200 to 620 kW/m 2 . For the minimum mass flux case, the highest aspect ratio channel with vapour venting membrane showed a maximum reduction of 60% in the two-phase pressure drop along with a 10% reduction in the heat transfer coefficient, compared to that without membrane. The lowest aspect ratio channel with vapour venting membrane showed a maximum increase of 30% in the two-phase heat transfer coefficient accompanied by a 10% reduction in the two-phase pressure drop, compared to that without membrane.